(untitled) (Journal of Engineering, 2011)
A flight simulation programme has been developed on a personal computer using Microsoft FORTRAN to simulate flight trajectories of a light aircraft by using Six-Degree-of-Freedom equation of motion. The simulation has been made realistic through pre-programmed the input to the control surfaces, atmospheric gust during the flight mode. The programme plays an important role in the evaluation and validation of the aircraft design process. A light aircraft (Cessna 182T) has been tested through free flight, gliding flight, flight with gust. The results show good trend and show that the programme could be dependent as a realistic flight test programme.